Hydrologic Response to Land Use and Land Cover Change Scenarios: An Example from the Paraopeba River Basin Based on the SWAT Model - Costa, Renata Cristina Araújo [UNESP]; Santos, Regina Maria Bessa; Fernandes, Luís Filipe Sanches [UNESP]; Carvalho de Melo, Marília [UNESP]; Valera, Carlos Alberto [UNESP]; Valle Junior, Renato Farias do [UNESP]; Silva, Maytê Maria Abreu Pires de Melo [UNESP]; Pacheco, Fernando António Leal [UNESP]; Pissarra, Teresa Cristina Tarlé [UNESP] (MDPI, 2023)
Human land use land cover changes (LULCCs) can cause impacts on watershed lands and on water resources. The regions with land use conflict suffer more intense erosion processes due to their high slope and drainage density. The study intends to evaluate scenarios with an absence of land use conflict and verify if it can contribute to reductions in surface runoff, avoiding the carriage of tailings to river channels. In the study, the SWAT model was used in the hydrological modeling of the Paraopeba River watershed affected by the rupture. The results show that the SWAT model was able to reproduce the flow data with good and very good performances. The quality indicators in the calibration step were NSE = 0.66, R2 = 0.69, PBIAS = 5.2%, and RSR = 0.59, and in the validation, step were NSE = 0.74, R2 = 0.77, PBIAS = 13.5%, and RSR = 0.51. The LULCC from 2000 to 2019 led to a 70% increase in lateral runoff (LATQ) and a 74% decrease in aquifer groundwater. The scenario of land use capability and no conflict can reduce lateral runoff by 37% and increase water infiltration by 265%, minimizing the point and diffuse contamination of the tailings in the Paraopeba river channel.
Keywords: Brumadinho dam; hydrological cycle; land use conflict; land use land cover changes; SWAT